Redefining Competition: Leveraging Advantages For Market Success - Dina Sarah Syahreza; Alya Audina; Tarisa Putri Artha; Tisa’ul Jannah; Juan Carmel Askelon (Universitas 45 Surabaya, 2024)
This research analyzes the role and impact of developing competitive advantage in the context of market success and company business strategy. The integration of findings from various case studies through qualitative and quantitative approaches provides a holistic picture of how competitive advantage influences consumer preferences and company performance. The research results highlight the significant influence of competitive advantage on consumer purchasing decisions. These findings, supported by Kotler's study and other research, confirm that when companies are able to offer significant added value, whether through product innovation, superior service, or smart marketing strategies, this influences consumers' purchasing choices. Adaptive planning strategies have also proven to be an important key in winning consumer preferences. The use of technology such as big data analytics is a significant element in identifying patterns, trends and relevant information that supports intelligent decision making. Overall, this research highlights that competitive development advantage is not only a goal for companies, but also a strategic foundation that supports overall business operations. This research offers an in-depth look at how competitive advantage is an important element in attracting consumers and maintaining a strong position in a competitive market.